2021
DOI: 10.1017/s1049023x21000509
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Decompression of Pneumothorax: A Systematic Review of Recent Evidence

Abstract: Introduction: Pneumothorax remains an important cause of preventable trauma death. The aim of this systematic review is to synthesize the recent evidence on the efficacy, patient outcomes, and adverse events of different chest decompression approaches relevant to the out-of-hospital setting. Methods: A comprehensive literature search was performed using five databases (from January 1, 2014 through June 15, 2020). To be considered eligible, studies required to report original data on deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Intervention by out of hospital providers may be critical in reducing mortality from tension PTX prior to definitive management (e.g., tube thoracostomy). Performance of needle thoracostomy (NT) is the traditional intervention for rapid treatment of tension physiology, but recent literature has called into question both the efficacy of thoracic decompression (Robitaille-Fortin, 2021;Axtman, 2019;Martin, 2012;Kaserer, 2017) and safety due to iatrogenic injuries sustained from placement of needle thoracostomy (e.g., cardiac, great vessel, lung).…”
Section: Introductionmentioning
confidence: 99%
“…Intervention by out of hospital providers may be critical in reducing mortality from tension PTX prior to definitive management (e.g., tube thoracostomy). Performance of needle thoracostomy (NT) is the traditional intervention for rapid treatment of tension physiology, but recent literature has called into question both the efficacy of thoracic decompression (Robitaille-Fortin, 2021;Axtman, 2019;Martin, 2012;Kaserer, 2017) and safety due to iatrogenic injuries sustained from placement of needle thoracostomy (e.g., cardiac, great vessel, lung).…”
Section: Introductionmentioning
confidence: 99%
“…Performance of nee-dle thoracostomy (NT) in the prehospital setting by medics is one approach to relieve tPTX. However, the efficacy of this procedure has recently been brought into question (Robitaille-Fortin, 2021;Axtman, 2019;Martin, 2012;Kaserer, 2017). The ability of NT to deliver successful and reliable decompression of the thoracic cavity in patients with suspected tPTX remains unclear (Robitaille-Fortin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of this procedure has recently been brought into question (Robitaille-Fortin, 2021;Axtman, 2019;Martin, 2012;Kaserer, 2017). The ability of NT to deliver successful and reliable decompression of the thoracic cavity in patients with suspected tPTX remains unclear (Robitaille-Fortin, 2021). Previous studies have shown a relatively high failure rate of NT to relieve tPTX (Axtman, 2019;Martin, 2012;Kaserer, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation